Environmental and Biological Determinants of Algal Lipids in Western Arctic and Subarctic Seas - Marmillot, Vincent; Parrish, Christopher C.; Tremblay, Jean-Éric; Gosselin, Michel; MacKinnon, Jenna F. (Frontiers in Environmental Science, 2020)
The Arctic is undergoing numerous environmental transformations. As a result of rising temperatures and additional freshwater inputs, ice cover is changing, with profound impacts on organisms at the base of food chains and consequently on the entire Arctic ecosystem. Indeed, phytoplankton not only provide energy as lipids, but also essential fatty acids (EFA) that animals cannot synthesise and must acquire in their diet. Omega-3 (ω3) and omega-6 (ω6) polyunsaturated fatty acids (PUFA) are essential for the healthy development and function of organisms. The high energy potential of monounsaturated fatty acids (MUFA) is of particular importance in cold waters, and various fatty acids including saturated fatty acids (SFA) are involved in organismal responses to environmental stressors. Yet relatively little is known of how variability or change in physicochemical seawater properties (e.g., temperature, light, salinity, pH and nutrients) may affect lipid synthesis in polar environments, either directly, by altering algal physiology, or indirectly, by promoting shifts in phytoplankton species composition. Here we investigated these two possibilities by sampling along a 3000-km transect spanning 28 degrees of latitude across the subarctic and Arctic domains of Canada. The taxonomic composition of phytoplankton mainly drove the FA profiles measured in particulate organic matter (POM). Strong, positive correlations between 16:1ω7 and diatoms were observed while the proportion of PUFA and ω6 FA increased with flagellate abundance. Among specific FAs, eicosapentaenoic acid (EPA; 20:5ω3) was positively correlated with diatoms but the expected relationship between docosahexaenoic acid (DHA; 22:6ω3) and dinoflagellates was not observed. Decreasing pH had a negative effect on EPA and MUFA proportions, and DHA proportions tended to decrease with higher temperature. These two effects were primarily driven by differences in phytoplankton assemblage composition. Overall, the results of this geographically extensive study provide new information into the use of lipid markers and the ecological determinants of FA synthesis in the North. It also highlights the importance of long-lived subsurface chlorophyll maximum layers in supplying PUFA-rich POM to the food web and suggests that this situation may persist despite ongoing changes in the physical environment.